Triptolide Attenuates Renal Tubular Epithelial-mesenchymal Transition Via the MiR-188-5p-mediated PI3K/AKT Pathway in Diabetic Kidney Disease - Xue, Mei (Int J Biol Sci, 2018)
Triptolide possesses the trait of renal protection. Epithelial-mesenchymal transition (EMT) is closely linked to the pathogenesis of diabetic kidney disease (DKD). MicroRNAs have recently emerged as critical regulators of DKD. However, it is poorly understood whether triptolide alleviates renal EMT by regulating microRNAs in DKD. In this study, we found that triptolide decreased albuminuria, improved the renal structure and reduced renal EMT in rats with DKD. Furthermore, activation of the PI3K/AKT signaling pathway was increased in diabetic rats, which was partly reversed by triptolide. Triptolide also alleviated glucose-induced EMT in HK-2 cells in vitro. PI3K/AKT signaling pathway activation was reduced after triptolide treatment. Moreover, triptolide decreased the increase in miR-188-5p expression stimulated by high glucose levels in HK-2 cells. miR-188-5p inhibited PTEN expression by directly interacting with the PTEN 3'-untranslated region. Additionally, downregulation of miR-188-5p, which imitates the effects of triptolide, attenuated the activation of the PI3K/AKT pathway and HG-induced EMT, whereas miR-188-5p overexpression reversed the effects of triptolide on the PI3K/AKT pathway and EMT. In conclusion, we demonstrated that triptolide ameliorates renal EMT via the PI3K/AKT signaling pathway through the interaction between miR-188-5p and PTEN, indicating that miR-188-5p may be a therapeutic target of triptolide in DKD.